The structured development of virtual environments: enhancing functionality and interactivity - Eastgate, Richard Mark (2001)
Desktop Virtual Reality (VR) is an easy and affordable way to implement VR technology within an organisation. It provides an experience that can be shared by many people, and its 3D, interactive capability facilitates the communication of ideas not possible using other media formats. There are a number of software toolkits available for the building and programming of Virtual Environments (VEs), but very few resources that can help developers acquire the skills and techniques required to give their VEs utility and usability. This thesis reviews existing research into VE design with an emphasis on interactivity and usability, and then uses a case study based approach to conceptualise the VE development process and develop exemplar guidance tools.